Senescence-Specific Expression of RAmy1A Accelerates Non-structural Carbohydrate Remobilization and Grain Filling in Rice (Oryza sativa L.) - Ouyang, Ning; Sun, Xuewu; Tan, Yanning; Sun, Zhizhong; Yu, Dong; Liu, Hai; Liu, Citao; Liu, Ling; Jin, Lu; Zhao, Bingran; Yuan, Dingyang; Duan, Meijuan (Frontiers in Plant Science, 2021)
Remobilization of pre-anthesis NSCs (non-structural carbohydrates) is significant for effective grain filling in rice (Oryza sativa L.). However, abundant starch particles as an important component of NSCs are still present in the leaf sheath and stem at the late stage of grain filling. There are no studies on how bioengineering techniques can be used to improve the efficiency of NSC remobilization. In this study, RAmy1A was expressed under the senescence-specific promoter of SAG12, which was designed to degrade starch in the leaf sheath and stem during grain filling. RAmy1A mRNA successfully accumulated in the leaf, stem, and sheath of transgenic plants after anthesis. At the same time, the starch and total soluble sugar content in the leaf, stem, and leaf sheath were obviously decreased during the grain-filling period. The photosynthetic rate of transgenic lines was higher than that of the wild types by an average of 4.0% and 9.9%, at 5 and 10 days after flowering, respectively. In addition, the grain-filling rate of transgenic lines was faster than that of the wild types by an average of 26.09%. These results indicate an enhanced transport efficiency of NSCs from source tissues in transgenic rice. Transgenic rice also displayed accelerated leaf senescence, which was hypothesized to contribute to decreased grain weight.